Molecular imaging by mass spectrometry — looking beyond classical histology - Schwamborn, Kristina; Caprioli, Richard M. (Nature reviews. Cancer, 2010)
Combining image analysis with mass spectrometry techniques provides new possibilities for molecular pathology. What are the applications of imaging mass spectrometry (IMS) using matrix-assisted laser desorption ionization (MALDI)? Imaging mass spectrometry (IMS) using matrix-assisted laser desorption ionization (MALDI) is a new and effective tool for molecular studies of complex biological samples such as tissue sections. As histological features remain intact throughout the analysis of a section, distribution maps of multiple analytes can be correlated with histological and clinical features. Spatial molecular arrangements can be assessed without the need for target-specific reagents, allowing the discovery of diagnostic and prognostic markers of different cancer types and enabling the determination of effective therapies.